2011
DOI: 10.1039/c1nr11109d
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism and determinants of nanoparticle penetration through human skin

Abstract: The ability of nanoparticles to penetrate the stratum corneum was the focus of several studies. Yet, there are controversial issues available for particle penetration due to different experimental setups. Meanwhile, there is little known about the mechanism and determinants of their penetration. In this paper the penetration of four model gold nanoparticles of diameter 6 and 15 nm, differing in surface polarity and the nature of the vehicle, through human skin was studied using multiphoton microscopy. This is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
113
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(119 citation statements)
references
References 57 publications
(71 reference statements)
5
113
1
Order By: Relevance
“…Nanosized particles with a large surface area could closely contact tissues and have better chances to penetrate bio-barriers and transport drugs in a more-controlled fashion. 26) Surfactant/water ratios greatly impacted on the size distributions as shown in Table 1. The size distribution of these 18 emulsions was in the range 1.45-448 nm.…”
Section: Resultsmentioning
confidence: 99%
“…Nanosized particles with a large surface area could closely contact tissues and have better chances to penetrate bio-barriers and transport drugs in a more-controlled fashion. 26) Surfactant/water ratios greatly impacted on the size distributions as shown in Table 1. The size distribution of these 18 emulsions was in the range 1.45-448 nm.…”
Section: Resultsmentioning
confidence: 99%
“…For each captured z-stack, optical layers incorporating cell-internalized liposomes were chosen and a z-projection image of the red channel (red fluorescence due to liposomes) was developed using ImageJ. The number of pixels was computed and converted into weighted number of liposomes as described previously [16,17] and as briefly referred to in the methodology of the adhesion experiments.…”
Section: Relative Liposomal Uptakementioning
confidence: 99%
“…22 Vehicle may alter the nature of skin barrier or even the physical state of NPs, which makes it another factor affecting NP penetration. 15 Labouta et al 23 studied the effect of DMSO on the penetration of gold NPs (AuNPs, φ=10 nm) in human skin and showed enhanced NP transport in the presence of DMSO. Kuo et al 24 demonstrated ethanol as an enhancer of zinc oxide NPs (φ=10 nm) in animal skin.…”
mentioning
confidence: 99%
“…It varied qualitatively in magnitude from none [31][32][33][34] to some NPs detected. 15,35,36 Differences may be affected by skin species, number of strips and type of tape used and/or NP characteristics. Our results noted that tape stripping (20 times) did not facilitate penetration of aqueous NPs (size 25-100 nm), thus NP skin penetration, even through barrier-impaired skin, is limited.…”
mentioning
confidence: 99%